Comunicar para "segurar o céu": diálogos com jovens comunicadores indígenas cearenses sobre suas narrativas - Girão, Ivna Nilton Marques (2024)
The research analyzes the narratives and perceptions of young indigenous communicators from Ceará about the production of content on social networks, building reflections and discussing the voices of communicators, the experiences and practices on the social network Instagram. The study provides an environment for the theoretical framework to talk to the philosophy of Ailton Krenak (2019) about the importance of "always being able to tell one more story", and the research is interested in a methodology of "listening and telling", with the objective that it is primarily of a qualitative nature, building qualitative analyses. All this, in order to think - based on interviews conducted with six young communicators - the presence of indigenous youth in a digital environment.